Applying Design Thinking to the Internet Cafe Booking Application Prototype - Ramadhana, Muhammad Wira; Irvan, Irvan; Nurjamiyah, Nurjamiyah (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2024)
Stream Cyber Café is one of the icafe in Medan, categorized as mid-high end due to its excellent services, facilities, and PC specifications for playing various online games. As a result, this icafe, founded by the STREAM UNIVERSE company, has a significant number of customers. The high number of customers often leads to a crowded and full environment, causing some customers to feel disappointed when they visit but cannot play because there are no available PCs. Therefore, this research aims to address the issues faced by internet cafe customers by designing a Prototype Internet Cafe Booking Application using the Design Thinking method. This prototype application will make it easier for internet cafe customers to check PC availability and book PCs using their smartphones. It will also provide valuable insights to the STREAM UNIVERSE company regarding an application that can enhance the quality of service at their icafe.